(untitled) (Applied Biological Research, 2025)
Heliotropium indicum L., locally known as “Venal pacha,” is an annual herbaceous weed belonging to the family Boraginaceae and is widely used in folk medicine. This study investigated the therapeutic potential of its root extract, focusing on antioxidant activity and cytotoxic effects on HT-29 colon cancer cells. Antioxidant activity of five solvent extracts was evaluated using DPPH and reducing power assays. The ethyl acetate extract, which exhibited superior antioxidant activity, was further subjected to cytotoxicity evaluation. Cytotoxicity against HT-29 cells was assessed using the MTT assay. Apoptosis and necrosis were analyzed through flow cytometry with Annexin V/PI staining, while cell cycle arrest was examined to determine the extract’s impact on cancer cell proliferation. The ethyl acetate extract demonstrated strong antioxidant activity in both assays, supporting its traditional use in oxidative stress-related gut health. MTT assay revealed potent cytotoxicity (82.76% inhibition at 100 µg mL⁻¹, IC₅₀ 3.04 µg mL⁻¹) with a dose-dependent response. Significant necrosis, particularly at lower doses, was observed, overshadowing apoptosis. Sub-G0 cell cycle arrest further indicated interference in cancer cell proliferation. Statistical analysis using SPSS (version 28) confirmed correlations between antioxidant activity and cytotoxicity. The findings suggest that H. indicum L. root possesses anticancer potential, primarily due to its necroptotic activity.